Android-Based Constuct 3 Educational Game Development With ADDIE Model To Improve Human Reproductive System Learning Outcomes - Ade Sekar Anggraini; Khairuna Khairuna (Universitas Labuhanbatu, 2025)
Background: The lack of interest and low learning outcomes of students in biology, especially in the complex and sensitive topic of the reproductive system, is the urgency of this study. Innovative media that can attract attention and suit the characteristics of the digital generation are needed. Therefore, this study aims to develop an Android-based educational game using Construct 3 on the subject of the human reproductive system for 11th grade high school students. Methodology: This research is a research and development (R&D) study using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The instruments used include expert validation sheets, teacher and student response questionnaires, and learning outcome tests, with data analysis conducted using descriptive qualitative and quantitative methods. Findings: The validation results showed that the media was highly valid, with a score of 87.5% from subject matter experts and 98.8% from media experts. The practicality test obtained a score of 92% from students and 97,5% from teachers, while effectiveness was indicated by an N-Gain value of 0.79 (high category). Contribution: These findings imply that Construct 3-assisted digital educational games are not only practical to integrate into biology learning but also effective in increasing student participation, motivation, and learning outcomes